Motivation, self-regulated learning, and their effects on learning outcomes of derivative materials during the Covid-19 pandemic - Analisa Fitria; Baiti Najihah; M. Amin Paris; Muh. Fajaruddin Atsnan; Maisea Ledua Nareki (Program Studi Pendidikan Matematika Program Pascasarjan Universitas Negeri Yogyakarta, 2021)
The study aims to identify the effect of learning motivation and self-regulated learning on learning achievement in “Derivative” learning materials in Trigonometry Functions. The study was field research using the ex-post facto design and quantitative approach during the Covid-19 Pandemic. The population was all grade XII students of a state Islamic senior high school in South Kalimantan, Indonesia. The samples of 24 students were selected using the purposive sampling technique. The data were gathered using a questionnaire and test and through documentation and interview. The data were analysed using the descriptive statistics and the inferential statistics consisting of normality test, linearity test, multicollinearity test, heteroscedasticity test, and multiple linear regression. The result shows that there is an effect of motivation and learning independence during the Covid-19 pandemic, which contributed 90.9% in increasing mathematics learning outcomes, and the rest was affected by other variables. This result is based on the results of F-test (Fcount = 104.948 Ftable =3.47) at the significance level of 5% with a multiple linear regression model Ῠ= 13.557+0.435 X1+0.395 X2 + ɛ.